Exposure to mercury among dental health workers in Turkey: Correlation with amalgam work and own fillings. (October 2015) - Yılmaz, Hınç; Tutkun, Engin; Demiralp, Kemal Ö; Yılmaz, Fatma M; Aliyev, Vugar; Söylemezoğlu, Tülin
Purpose: To investigate the current status of exposure to mercury (Hg) among dental health workers in Turkey. Methods: A total of 115 persons working in the same hospital were included in the study and were divided into three groups. Group 1 consisted of 67 dentists; group 2 consisted of 21 dental personnel who work with amalgam, and group 3 consisted of 27 control subjects who work in the same hospital but are non-dental personnel. The number of amalgam fillings that have been made by the dentists and the number of own fillings of the subjects were recorded. Results: Plasma Hg levels were found to be 3.76 ± 1.84, 3.54 ± 1.83, and 2.69 ± 0.97 µg/L in groups 1, 2, and 3, respectively. Hg concentrations in group 1 were significantly higher than the control group. There was no significant difference between groups 1 and 2. The number of amalgam fillings made by the dentists in the previous year correlated significantly with plasma Hg levels ( r = 0.378, p < 0.01). There was no significant correlation between the own amalgam fillings in the teeth of the subjects and Hg levels. Conclusion: Preventive measures for protection from exposure to Hg are necessary for occupational health in dentistry and proper industrial hygiene rules should be emphasized to avoid contamination during work.